2004
DOI: 10.4049/jimmunol.172.1.40
|View full text |Cite
|
Sign up to set email alerts
|

A Role for TCR Affinity in Regulating Naive T Cell Homeostasis

Abstract: Homeostatic signals that control the overall size and composition of the naive T cell pool have recently been identified to arise from contact with self-MHC/peptide ligands and a cytokine, IL-7. IL-7 presumably serves as a survival factor to keep a finite number of naive cells alive by preventing the onset of apoptosis, but how TCR signaling from contact with self-MHC/peptide ligands regulates homeostasis is unknown. To address this issue, murine polyclonal and TCR-transgenic CD8+ cells expressing TCR with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
218
1
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 219 publications
(232 citation statements)
references
References 30 publications
7
218
1
6
Order By: Relevance
“…A recent report has also shown that CD8 lo cells can in fact expand in a major histocompatibility complex (MHC) class I-deficient host. 22 In our experiments, we showed that CD8 lo cells could expand in female recipients, and they underwent one extra division in male recipients. CD8 int cells, on the other hand, were much more dependent on the male antigen for proliferation since they underwent about 3 fewer divisions in female recipients.…”
Section: Role Of Antigen In the Expansion Of Cd8 Lo Cells In Vivomentioning
confidence: 81%
See 1 more Smart Citation
“…A recent report has also shown that CD8 lo cells can in fact expand in a major histocompatibility complex (MHC) class I-deficient host. 22 In our experiments, we showed that CD8 lo cells could expand in female recipients, and they underwent one extra division in male recipients. CD8 int cells, on the other hand, were much more dependent on the male antigen for proliferation since they underwent about 3 fewer divisions in female recipients.…”
Section: Role Of Antigen In the Expansion Of Cd8 Lo Cells In Vivomentioning
confidence: 81%
“…23 By contrast, CD8 hi cells could not expand in irradiated female mice as interactions between the H-Y TCR and female self-peptides/H-2D b alone are insufficient for the expansion of CD8 hi cells in vivo. 22,24 CD8 hi cells proliferated most efficiently in irradiated male mice.…”
Section: Role Of Antigen In the Expansion Of Cd8 Lo Cells In Vivomentioning
confidence: 99%
“…However, it is also possible that episodes of lymphopenia targeting subpopulations of cells in defined tissues are common during normal life, as a result of exposure to infectious agents, cytotoxic compounds, radiation or apoptosis-inducing signals. Considering that, during homeostatic expansion, T cell clonotypes with increased affinity for highly represented ligands have a selective advantage (32)(33)(34) and acquire a preactivated phenotype (9), it is conceivable that homeostatic proliferation is a mechanism that evolved, in part, to allow a rapid resetting of the lymphocyte repertoire for faster and more efficient immune responses. In support of this possibility, we (35) and others (36,37) have shown that homeostatic expansion concurrent with immunization generates T cell populations enriched for CD8 ϩ effectors with enhanced antitumor activities.…”
Section: Discussionmentioning
confidence: 99%
“…TCR Tg naïve T cells that bind self-pMHC with greater affinity have been shown to proliferate more extensively in lymphopenic environments [14][15][16]. Some TCR Tg T cells divide extremely poorly or not at all while others undergo more than 6 divisions upon adoptive transfer within the first 1-2 weeks.…”
Section: Self-pmhc Reactivity Dictates the Intensity Of Competition Dmentioning
confidence: 99%
“…This suggests that signals obtained from sub-threshold interactions with self-pMHC are a limiting resource for which T cells with the same specificity compete. Interestingly, there is heterogeneity in the number of divisions distinct clonotypes undergo in T-cell deficient hosts [14][15][16]. It has previously been assumed that intrinsic differences dictate whether or not a TCR clonotype is capable of homeostatic expansion, with some T cells having a self-reactivity that is simply too low to obtain enough signal from MHC interactions to lead to division [2,3,17].…”
Section: Introductionmentioning
confidence: 99%